Way forward from the experiences of disaster preparedness and response at Patan Hospital during 2013-2020: Nepal - Shrestha, Ashis; Bajracharya, Sumana; Phuyal, Naveen; Shrestha, Bikal; Maharjan, Kripa (Journal of General Practice and Emergency Medicine of Nepal, 2020)
The history of the disaster management plan at Patan Hospital goes back to 1995 AD (2051 BS). The plan was first written by Dr. Cleve Chevassut. This was a hospital-based disaster management plan and consisted of a hospital incident command system (HICS), triaging, patient flow, job description, and management protocol. This plan was regularly updated and tested with disaster drills. In the year 2013, the 10th revision of the disaster management plan was done. This plan was tested with a disaster drill and the template of this plan was circulated to different hospitals of Nepal. This document consists of a part of experiences and evidence of hospital-based disaster activity that took place inside Patan hospital and activities to establish hospital-based disaster management plan in different hospitals of the country from 2013 to 2020. This document does not cover the overall preparedness response of all hospitals and that of the country.